1994
DOI: 10.1016/0014-5793(94)80468-0
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of low density lipoprotein by cells or iron is inhibited by zinc

Abstract: We have examined the effect of zinc ions on low density lipoprotein (LDL) oxidation by macrophages, endothelial cells and iron ions in terms of the increased uptake of the LDL by macrophages. Zinc ions inhibited LDL modification by both cell types (which is dependent on the presence of iron ions in the culture medium) and by iron ions alone. As oxidised LDL is believed to be involved in atherogenesis, this raises the possibility that zinc may be an endogenous protective factor against atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Zn2+ is a known inhibitor of endogenous plasma GSH-Px (21) that, unlike transition metal ions, does not promote free radical generation (22,23). In addition, ZnCl2 inhibits the plasma but not the erythrocyte form of GSH-Px, excluding the possibility that the results obtained were due to erythrocyte contamination.…”
Section: Measurement Ofmentioning
confidence: 99%
“…Zn2+ is a known inhibitor of endogenous plasma GSH-Px (21) that, unlike transition metal ions, does not promote free radical generation (22,23). In addition, ZnCl2 inhibits the plasma but not the erythrocyte form of GSH-Px, excluding the possibility that the results obtained were due to erythrocyte contamination.…”
Section: Measurement Ofmentioning
confidence: 99%
“…3,4 These data are consistent with some, but not all, epidemiological studies on the potential links between iron and cardiovascular disease. [5][6][7][8] Zinc ions have been reported to modulate oxidant damage via the displacement of iron and copper from oxidationsensitive sites on erythrocyte membranes, 9 LDL, 10 or liposomes. 11 Epidemiological data indicate that elevated serum zinc levels may be protective against disease.…”
mentioning
confidence: 99%
“…27 Zn may play an antiatherogenic role through the inhibition of inflammation and oxidative stress, consequently inhibiting the oxidation of LDL particles by macrophages and endothelial cells. 20,[28][29][30] LDL(-) (a lipid peroxidation marker) induces atherogenesis by a variety of biological activities including cytotoxicity and leukocyte recruitment that actively contribute to the alteration of the vascular endothelium, increasing CV risk. [8][9][10] Many reports have described the increased LDL(-) levels in patients with CV disease risk, including CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, cellular enrichment with Zn has been shown to attenuate or prevent TNF-induced endothelial cell injury. 32 According to Meerarani et al, 29 Zn deficiency increases apoptotic cell death induced by TNF-α, and these authors have showed that Zn supplementation attenuates apoptosis. Moreover, several potential mechanisms may account for the benefits of Zn, the increased activity and the expression of stress-related proteins and antioxidant proteins, including metallothioneins (MT), chaperones, ApoJ, Poly (ADP-Ribose) polymerase-1 (PARP-1) methionine sulfoxide reductase (Msr), and superoxide dismutase (SOD).…”
Section: -13mentioning
confidence: 99%